Neurocognitive Effects of Preceding Facial Expressions on Perception of Subsequent Emotions - Kim, Shin Ah; Kim, Sang Hee (Frontiers in Behavioral Neuroscience, 2021)
In everyday life, individuals successively and simultaneously encounter multiple stimuli that are emotionally incongruent. Emotional incongruence elicited by preceding stimuli may alter emotional experience with ongoing stimuli. However, the underlying neural mechanisms of the modulatory influence of preceding emotional stimuli on subsequent emotional processing remain unclear. In this study, we examined self-reported and neural responses to negative and neutral pictures whose emotional valence was incongruent with that of preceding images of facial expressions. Twenty-five healthy participants performed an emotional intensity rating task inside a brain scanner. Pictures of negative and neutral scenes appeared, each of which was preceded by a pleasant, neutral, or unpleasant facial expression to elicit a degree of emotional incongruence. Behavioral results showed that emotional incongruence based on preceding facial expressions did not influence ratings of subsequent pictures’ emotional intensity. On the other hand, neuroimaging results revealed greater activation of the right dorsomedial prefrontal cortex (dmPFC) in response to pictures that were more emotionally incongruent with preceding facial expressions. The dmPFC had stronger functional connectivity with the right ventrolateral prefrontal cortex (vlPFC) during the presentation of negative pictures that followed pleasant facial expressions compared to those that followed unpleasant facial expressions. Interestingly, increased functional connectivity of the dmPFC was associated with reduced modulatory influence of emotional incongruence on the experienced intensity of negative emotions. These results indicate that functional connectivity of the dmPFC contributes to the resolution of emotional incongruence, reducing the emotion modulation effect of preceding information on subsequent emotional processes.